The Potential of Mango Lipstick Leaves as Natural Bar Soap Extract: The Latest Innovation of Environmentally Friendly Products - Ririn Risnawati; Rinita Setiani; Nurul Chamidah; Subhan Haris (Ann Publisher, 2023)
The Potential of Mango Gincu Leaves as Natural Bar Soap Extract: The Latest Innovationof Environmentally Friendly Products. Soap is an item used in everyday human life that is useful forcleaning the body from microbes and germs. Mango leaves have natural ingredients that haveantimicrobial and antioxidant properties so that they can be used as ingredients in makingenvironmentally friendly soap. Making soap from mango leaf extract aims to bring out the potentialof mango leaves as an effective soap preparation as a cleanser and maintain body hygiene. Thismethod of community service activities uses socialization lectures and demonstrations of the stagesof making bar soap from Gedong Gincu Mango leaf extract. The primary data in this study wasobtained from the results of socialization and demonstrations in the field. Literature review ofprevious research, used as a secondary data source. The results of community service activitiesobtained increased insight and practice of making bar soap from mango leaf extract and increasedawareness of the importance of maintaining hygiene and sanitation. The impact received by thecommunity is in the form of increasing the spirit of innovation and creativity in developing villagepotential